Studies of Madagascan Ptiliidae (Coleoptera) 4: The genus Bambara including eight new species and the first account of blindness and aptery in the genus - Darby, Michael (Zootaxa, 2014)
This is the fourth report detailing Ptiliidae collected from forest litter by the Moravian Museum (Brno, Czech Republic) expeditions to Madagascar 2010–2013. Eight new species are described and figured: B. edwardi sp. n.; B. lanquidula sp. n.; B. merina sp.n.; B. opaca sp. n.; B. problematica sp. n.; B. secubita sp. n.; B. thomasi sp. n. and B. verecunda sp. n., and new data recorded for  B. dybasi Johnson. Problems concerning the genital morphology and species determination of the parthenogenetic members of the genus are discussed in relation to the findings, and the first blind and apterous species reported.A key to the known species from the island is provided.